A cosmopolitan fungal pathogen of dicots adopts an endophytic lifestyle on cereal crops and protects them from major fungal diseases - Tian, Binnian; Xie, Jiatao; Fu, Yanping; Cheng, Jiasen; Li, Bo; Chen, Tao; Zhao, Ying; Gao, Zhixiao; Yang, Puyun; Barbetti, Martin J.; Tyler, Brett M.; Jiang, Daohong (The ISME Journal, 2020)
Fungal pathogens are seriously threatening food security and natural ecosystems; efficient and environmentally friendly control methods are essential to help safeguard such resources for increasing human populations on a global scale. Here, we find that Sclerotinia sclerotiorum , a widespread pathogen of dicotyledons, can grow endophytically in wheat, rice, barley, maize, and oat, providing protection against Fusarium head blight, stripe rust, and rice blast. Protection is also provided by disabled S. sclerotiorum strains harboring a hypovirulence virus. The disabled strain DT-8 promoted wheat yields by 4–18% in the field and consistently reduced Fusarium disease by 40–60% across multiple field trials. We term the host-dependent trophism of S. sclerotiorum , destructively pathogenic or mutualistically endophytic, as schizotrophism. As a biotroph, S. sclerotiorum modified the expression of wheat genes involved in disease resistance and photosynthesis and increased the level of IAA. Our study shows that a broad-spectrum pathogen of one group of plants may be employed as a biocontrol agent in a different group of plants where they can be utilized as beneficial microorganisms while avoiding the risk of in-field release of pathogens. Our study also raises provocative questions about the potential role of schizotrophic endophytes in natural ecosystems.